The Renaissance of Alkali Metabisulfites as SO2 Surrogates - Sahoo, Ashish Kumar; Dahiya, Anjali; Rakshit, Amitava; Patel, Bhisma K. (SynOpen, 2021)
The upsurge of interest in the development of methodologies for the construction of sulfur-containing compounds via the use of expedient reagents has established sustainable tools in organic chemistry. This review focuses on sulfonylation reactions using inorganic sulfites (Na2S2O5 or K2S2O5) as the sulfur dioxide surrogates. Compared to the bis-adduct with DABCO, which is an excellent surrogate of gaseous SO2, the use of sodium or potassium metabisulfites as SO2 surrogates are equally efficient. The objective of the current review is to exemplify recent sulfonylation reactions using inorganic sulfites. For better understanding, the review is categorized according to the mode of reactions: transition-metal-catalyzed SO2 insertion, metal-free SO2 insertion, and visible-light-mediated SO2 insertion. All the reactions in each of the sections are illustrated with selected examples with a pertinent explanation of the proposed mechanism.1 Introduction2 Outlines of the Reactions Involving SO2 Insertion2.1 Transition-Metal-Catalyzed SO2 Insertion2.2 Transition-Metal-Free SO2 Insertion2.3 Visible-Light-Mediated SO2 Insertion3 Conclusion and Outlook
Keywords: DABCO·(SO2)2; sodium or potassium metabisulfite; SO2 surrogate; sulfonylation reaction; SO2 insertion